The massive Wolf-Rayet binary LSS 1964 (=WR 29) - Gamen, Roberto Claudio (2009)
Context. WR 29 is a known WN7h+O double-lined binary system with a rather short period (3.164 days). Aims. We search for light variations to determine the inclination of the system and thus the absolute masses of both components. Methods. We observed photometrically the field of WR 29 between December, 2002, and February, 2006. Results. We find that the light of WR 29 varies in phase with the spectroscopic period of 3.16412 days, presenting two minima corresponding to the conjunctions of the binary components. Numerical models fitted to the light curve indicate an orbital inclination of about 44°, and masses of 53 M⊙ and 42 M⊙ for the O-and WN-type components, respectively.